VI.i. Newspaper cuttings, - Kennedy, John Pitt, 1796-1879 (1843)
Cuttings from various newspapers of interest or pertaining to the Kennedy family. Includes cuttings concerning John Pitt Kennedy and public works in Ireland, particularly the Waterford and Limerick railway lines, as well as cuttings concerning his donation of £600 towards arming Orangemen in Dublin. Also included are cuttings concerning Kennedy's engineering work in India and the military successes of Sir Charles Napier. Published letters between Napier's brother William and Sir James Outram, engaged in dispute over alleged defamation of Sir Charles Napier, are also included.